Religious Leaders and Moral Disengagement: An Examination of Followers' Authoritarian Attitudes - Wulandari, Roosalina; Arifin, Haykal Hafizul (Jurnal Psikologi Islam dan Budaya, 2026)
Religious leaders often hold revered positions and shape moral norms within their communities. However, obedience to such figures may become problematic when followers fail to question unethical behavior or the misuse of authority. This study investigates how dimensions of right-wing authoritarianism (submission, aggression, and conventionalism) and mechanisms of moral disengagement relate to perilous obedience toward religious authority. Drawing on data from 243 Indonesian participants across majority and minority religious groups, hierarchical regression analyses showed that authoritarian submission and moral disengagement - particularly advantageous comparison - were the strongest predictors of perilous obedience. Although authoritarian aggression initially predicted the outcome, its effect diminished once moral disengagement was entered into the model. Conventionalism, despite its theoretical importance, did not significantly predict obedience in this context. These findings highlight psychological factors associated with followers’ willingness to tolerate or justify the misuse of authority in religious settings.